A new Android Application Framework (AAF) for API PM2.5 data management system. Issue 1 (1st April 2022) - Sadun, A S; Rosli, M A; Hashim, N H; Sukor, J A; Othman, N; Cheng, N K; Si, T C; Ning, C Y
Abstract: Air Pollution Index (API) is used in Malaysia to measure the ambient air quality and PM2.5 is one of its parameters for ambient air quality monitoring. However, most of the PM2.5 samplers available for research and monitoring by universities and monitoring providers are in manual mode in which the data was logged into the equipment data logger and was manually extracted to the personal computer before analysis. Therefore, this project is aimed to propose an Android Application Framework (AAF) containing IoT devices to monitor the real-time ambient air quality and disseminate computed API information through the social media platform. In this study, mobile apps which are Blynk was used and enabled the user to control remotely desirable outcomes at any time. E-sampler IoT interface, mobile application, data management, data management system, API judgment and information dissemination are proposed to make AAF succeed. As a result, the proposed AAF has been fully utilized in obtaining real-time pollutants data and finally analyzing PM2.5 to obtain real-time API information. IoT device has successfully interface with E-Sampler, to obtain raw data and be able to be downloaded for further analysis. In conclusion, AAF has functioned great and information was disseminated to the public through social media.